2015
DOI: 10.1016/j.ajpath.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte and Macrophage Plasticity in Tissue Repair and Regeneration

Abstract: Heterogeneity and high versatility are the characteristic features of the cells of monocyte-macrophage lineage. The mononuclear phagocyte system, derived from the bone marrow progenitor cells, is primarily composed of monocytes, macrophages, and dendritic cells. In regenerative tissues, a central role of monocyte-derived macrophages and paracrine factors secreted by these cells is indisputable. Macrophages are highly plastic cells. On the basis of environmental cues and molecular mediators, these cells differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
510
0
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 606 publications
(534 citation statements)
references
References 115 publications
12
510
0
12
Order By: Relevance
“…An additional possibility is that other cell types transdifferentiate into LECs, as has been shown in the case of tumor-related blood vessels (Kirschmann et al, 2012;Soda et al, 2011) and in tissue regeneration (reviewed by Das et al, 2015). It has also been shown, for example, that bone marrow-derived cells, and myeloid cells in particular, can contribute to lymphatic vessel growth under pathological conditions (Maruyama et al, 2005).…”
Section: Implications For Disease and Regenerationmentioning
confidence: 99%
“…An additional possibility is that other cell types transdifferentiate into LECs, as has been shown in the case of tumor-related blood vessels (Kirschmann et al, 2012;Soda et al, 2011) and in tissue regeneration (reviewed by Das et al, 2015). It has also been shown, for example, that bone marrow-derived cells, and myeloid cells in particular, can contribute to lymphatic vessel growth under pathological conditions (Maruyama et al, 2005).…”
Section: Implications For Disease and Regenerationmentioning
confidence: 99%
“…Such cellular transition is commonly exhibited not only by stem cells but also by blood-borne monocytederived macrophages. Das et al 14 have addressed the significance of plasticity in macrophages and monocytes and their relevance to tissue regeneration and repair.…”
Section: Cellular Plasticitymentioning
confidence: 99%
“…Broadly, both classical and intermediate monocytes are able to exhibit inflammatory properties (14,15). Elevated CD16 + monocytes were observed during bacterial infections (14).…”
Section: Monocyte/macrophages Linage: the First Line Of Immune Defencementioning
confidence: 99%
“…Macrophage phenotypes and functions vary with their anatomical locations (15). in a year in mice (27), however, no studies till date reported about the half-life of human AMs.…”
Section: Macrophage: a Multi-role Immune Cellmentioning
confidence: 99%
See 1 more Smart Citation